Efektivitas Pembelajaran Daring Mahasiswa Pendidikan Matematika pada Masa Pandemi Covid-19 - Rahmawati, Fitriana (STKIP PGRI Bandar Lampung, 2022)
The Corona outbreak has made everything change routine, including in terms of education. In the past, learning in universities was carried out face-to-face, but now learning must be carried out online. The purpose of this study was to find out how much effective online learning was during the COVID-19 pandemic for students. This study uses an exploratory descriptive approach in the scope of qualitative research. The research subjects were active students of the mathematics education study program STKIP PGRI Bandar Lampung semester 2 and 4 of the 2020/2021 academic year. The research data was obtained by using a questionnaire in the form of a google form which was filled in by the 2 and 4 semester students via a smartphone or laptop. The data obtained were analyzed descriptively, starting with grouping based on the category of responses, then describing the different responses from students. This study found obstacles in the online learning process, namely students' economic problems that could affect the ownership of mobile phones as the main support for online learning, constraints on internet packages or wifi networks, and poor networks in the student environment. The results of the research can be concluded that online learning is not effective.